Pseudoscience : The Conspiracy Against Science - Kaufman, James C.; Kaufman, Allison B., 1976- (Book collections on Project MUSE., 2018)
"In a post-truth, fake news world, we are particularly susceptible to the claims of pseudoscience. When emotions and opinions are more widely disseminated than scientific findings, and self-proclaimed experts get their expertise from Google, how can the average person distinguish real science from fake? This book examines pseudoscience from a variety of perspectives, through case studies, analysis, and personal accounts that show how to recognize pseudoscience, why it is so widely accepted, and how to advocate for real science."--Back cover